Motivation to Reduce Drinking and Engagement in Alcohol Misuse Treatment in Alcohol-Related Liver Disease: A National Health Survey. (29th June 2022) - Kann, Anna Emilie; Jepsen, Peter; Madsen, Lone Galmstrup; Crooks, Colin; Fleming, Kate; Christensen, Anne Illemann; Lau, Cathrine Juel; West, Joe; Askgaard, Gro
Abstract : INTRODUCTION: The study aim was to identify predictors of motivation to reduce alcohol consumption and whether motivation predicts engagement in alcohol misuse treatment in alcohol-related liver disease (ALD). METHODS: Data from health surveys and health-care registries were combined. RESULTS: Of 674 patients with ALD, 65% consumed alcohol. Recent hospital admission and severe alcohol problems were associated with motivation to reduce alcohol consumption. Two-year probability for engagement in misuse treatment was 29% for patients with motivation to reduce alcohol consumption versus 6.5% for patients without motivation. DISCUSSION: ALD patients with recent hospital admission were more motivated to cut down alcohol consumption, and motivation predicted engagement in alcohol misuse treatment. This insight can help us target brief interventions.